Contextualized acceleration and deceleration profiles of elite soccer players during English Premier League match-play. The effect of possession, positional demands and opponent ranking - Morgans, Ryland; Mandorino, Mauro; Ryan, Ben; Zmijewski, Piotr; Moreira, Alexandre; Oliveira, Rafael (Biology of Sport, 2025)
This study aimed to compare accelerations (ACC) and decelerations (DEC) when in- ( IP ) and outof-possession ( OP ) during official English PremierLeague (EPL) match-play over three consecutive seasonsconsidering playing position, match location and opponent ranking. Match data from 31 male professional soccer players was obtained via an optical tracking system. Playing position significantly influenced ACC IP , DEC IP , and DEC OP . Ranking difference and match location were significant predictors for DEC IP , ACC OP , and DEC OP . An increase in ranking difference was associated with higher DEC IP . Conversely, in the out-of-possession phase (ACC OP and DEC OP ), a decrease in these parameters with increasing ranking difference was observed. Regarding match location, positive β coefficientssuggested that DEC IP , ACC OP , and DEC OP values were significantly higher during away matches compared to home matches. A significant interaction (playing position×ranking difference) was reported for DEC OP (β = 0.035, p = 0.013). Interestingly, DEC OP actions decreased with increasing ranking difference across all playing positions except for wingers. In conclusion, these findings highlight that distinct contextual factors influence ACC and DEC performance during in- and out-of-possession phases of EPL match-play.